Apical myosin XI anticipates F‐actin during polarized growth of Physcomitrella patens cells. (26th November 2012) - Furt, Fabienne; Liu, Yen‐Chun; Bibeau, Jeffrey P.; Tüzel, Erkan; Vidali, Luis
Summary Tip growth is essential for land colonization by bryophytes, plant sexual reproduction and water and nutrient uptake. Because this specialized form of polarized cell growth requires both a dynamic actin cytoskeleton and active secretion, it has been proposed that the F‐actin‐associated motor myosin XI is essential for this process. Nevertheless, a spatial and temporal relationship between myosin XI and F‐actin during tip growth is not known in any plant cell. Here, we use the highly polarized cells of the moss Physcomitrella patens to show that myosin XI and F‐actin localize, in vivo, at the same apical domain and that both signals fluctuate. Surprisingly, phase analysis shows that increase in myosin XI anticipates that of F‐actin; in contrast, myosin XI levels at the tip fluctuate in identical phase with a vesicle marker. Pharmacological analysis using a low concentration of the actin polymerization inhibitor latrunculin B showed that the F‐actin at the tip can be significantly diminished while myosin XI remains elevated in this region, suggesting that a mechanism exists to cluster myosin XI‐associated structures at the cell's apex. In addition, this approach uncovered a mechanism for actin polymerization‐dependent motility in the moss cytoplasm, where myosin XI‐associated structures seem to anticipate and organize the actin polymerization machinery. From our results, we inferred a model where the interaction between myosin XI‐associated vesicular structures and F‐actin polymerization‐driven motility function at the cell's apex to maintain polarized cell growth. We hypothesize this is a general mechanism for the participation of myosin XI and F‐actin in tip growing cells.